The Trend Synthesis Thin Film Research as Electronic Device (A Review) - Aris Doyan; Susilawati; Agus Abi Purwoko; Ibrahim; Sukainil Ahzan; Sifaul Gummah; Bahtiar; Muhammad Ikhsan (Jurnal Penelitian Pendidikan IPA, 2023)
A thin film is a material with optical properties highly dependent on the dielectric constant, refractive index, and gap energy. This research aims to identify and analyze research trends in thin-layer synthesis as electronic devices. This research is qualitative. The data used in this research was obtained from documents indexed by Google Scholar from 2014-2023 using Publish or Perish and Dimension.ai. Research procedures use PRISMA guidelines. The data identified and analyzed included the type of publication, author on thin layer synthesis, source of publication, and the title of research on thin layer synthesis that was widely cited. The data analysis method uses bibliometric analysis assisted by VOSviewer software. The results of the study show that the research trend in thin-layer synthesis has experienced a fluctuating increase from 2014 to 2020. The journal containing the most thin-layer synthesis articles is ECS Meeting Abstracts with 676. The results of the density mapping analysis show that the theme that is rarely researched is organic semiconductors, organic thin film transistors, and green synthesis.